AN EFFECTIVENESS OF CONSUMERS' BRAND SWITCHING TOWARDS ENVIRONMENTALLY FRIENDLY SKINCARE PRODUCTS IN DKI JAKARTA AREA - Firsan Nova; Melani Quintania; Ellena Nurfazria Handayani; Resa Nurlaela Anwar; Khusnul Khotimah (Jurnal Apresiasi Ekonomi, 2025)
This research aims to examine the effectiveness of consumer brand switching for environmentally friendly skincare products in the DKI Jakarta area, in terms of brand personality, online customer reviews, and variety seeking. This type of research is associative with a quantitative approach. The population includes consumers who use environmentally friendly body care products in the DKI Jakarta area. A purposive sampling technique was used in this research with the final sample set at 100 respondents. The data analysis technique in the research uses multiple regression. The effectiveness of brand switching is influenced by the three factors above simultaneously. Brand Personality and Online Customer Reviews do not have a significant influence on Brand Switching for environmentally friendly skincare products, while there is a significant influence on Variety Seeking.Keyword: brand switching, effectiveness, variety seeking